Clinical observation of the efficacy and mechanism of the Wenfei Jiangzhuo formula in lung and kidney deficiency-type vascular dementia. Issue 1 (1st January 2020) - Hu, Yueqiang; Chen, Wei; Wu, Lin; Jiang, Lingfei; Chen, Lianmei; Tang, Nong
Abstract : To explore the clinical efficacy and mechanism of the Wenfei Jiangzhuo formula in lung and kidney deficiency-type vascular dementia. The study was conducted from March 2014 to March 2016. Eighty-four patients with lung and kidney deficiency-type vascular dementia were divided into the observation ( n = 44) and control ( n = 40) groups. The control group received oral donepezil hydrochloride, while the observation group received the Wenfei Jiangzhuo formula. The mini-mental state examination (MMSE) score, activities of daily living (ADL) scale score, and serum superoxide dismutase (SOD) and malondialdehyde (MDA) levels were assessed before and after treatment. The MMSE and ADL scale scores in the two groups significantly improved after treatment ( P < 0.05); the scores in the observation group were significantly higher than those in the control group ( P < 0.05). The SOD levels in both groups significantly improved, and there was a significant difference in the MDA levels in both groups ( P < 0.05). The SOD and MDA levels improved more significantly in the observation group than in the control group ( P < 0.05). The Wenfei Jiangzhuo formula has a good curative effect in patients with lung and kidney deficiency-type vascular dementia and may improve MMSE and ADL scale scores and patient satisfaction.